PERANCANGAN USER INTERFACE WEBSITE KATERING “AROMA BOGA” DI GUNUNGKIDUL MENGGUNAKAN METODE DESIGN THINKING - Prajarini, Dian; Malih, Fauzan Hanafi (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2025)
Catering is a business that involves the preparation, cooking, and service of food for various events on a large scale. Aroma Boga is a catering business that specializes in serving snack and meal boxes. In the current landscape of numerous digital platforms, Aroma Boga capitalizes on this by marketing its products through various government platforms. However, these efforts may not be deemed sufficient to effectively reach the target audience and optimize Aroma Boga's services. This research employed the design thinking method to develop a website interface. The results of this study demonstrate that the website interface design exhibits high usability, as confirmed by usability testing.